TRADISI PESANTREN SEBAGAI BENTENG MORAL DAN BUDAYA BANGSA - Siti Zulaika; M Fadhil Uzmi; M Iqbal (Jurnal Recoms, 2025)
This study examines the role of pesantren traditions as moral and cultural safeguards in Indonesia amid increasing social and technological changes. The research aims to analyze how pesantren practices such as discipline, clerical role modeling, communal life, and ritual activities shape students’ moral character and preserve local cultural values. Using a library research method with critical analysis, this study reviews open-access national publications from 2019–2024 to map relevant concepts and findings. The results show that pesantren traditions function as effective instruments for internalizing moral values while simultaneously maintaining local cultural heritage. However, pesantren face challenges from modernization, digital exposure, and shifting youth lifestyles, requiring adaptive strategies to remain relevant. In this context, pesantren are encouraged to reinterpret and reconstruct their traditions without losing their traditions without losing their fundamental moral and cultural principles. Adaptive efforts such as contextual learning, cultural acculturation, and the integration of contemporary social realities are necessary to ensure the sunstainability of pesantren traditions. The study concludes that pesantren possess strong potential as moral and cultural fortresses, provided they continue to reconstruct traditions in a contextual and transformative manner in response to ongoing social change.